Genetic Variability And Interrelationship Analysis Of Quantitative Traits In Rice (Oryza Sativa L.) Germplasm (Applied Biological Research, 2020)
The present investigation was carried out to assess the genetic variability  parameters, correlation and path analysis in 95 elite rice germplasm  collections for 12 yield and its contributing traits during kharif, 2018 in a  randomized block design, replicated twice. Theanalysis of variance for  mean sum of squares due to genotypes showed significant differences for  all the quantitative characters studied at 1 and 5% level of significance. PCV and GCV were high for traits like days to 50% flowering, tillers plant1, productive tillers plant-1, length/breadth ratio and grain yield plant-1. High heritability (> 60%) coupled with high genetic advance as percentage  of mean (> 30%) was recorded for days to 50% flowering, leaf length,  tillers plant-1, productive tillers plant-1, L/B ratio, grain width, 100 grain  weight and grain yield plant-1indicating thepreponderance of additive gene action. The grain yield plant-1 had highly significant and positive  correlation both at genotypic and phenotypic levels with tillers hill-1, productive tillers plant-1, panicle length and days to 50% flowering. High  direct effects of these characters appeared to be the main reason for their  strong association with grain yield except for number of productive tillers  plant-1 which had strong association with yield through indirect effect (i.e.  through tillers plant-1. Hence, direct selection for these characters would  be very effective for further improvement of grain yield in rice and for the  selection of elite genotypes.
Keywords: Correlation; germplasm; path analysis; quantitative traits; rice; variability